2013
DOI: 10.5489/cuaj.458
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of penile cancer in situ metastasizing to lymph nodes

Abstract: Fax 875-0205Mail CUAJ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…MRI is mainly indicated in major lesions of the penis when the clinical examination becomes difficult and cannot accurately determine the infiltration of the cavernous body [4] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI is mainly indicated in major lesions of the penis when the clinical examination becomes difficult and cannot accurately determine the infiltration of the cavernous body [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Cavernosography is an aggressive examination, used in old series for the proximal evaluation of tumor extension and currently has no place in the assessment of tumors of the penis [4] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that routine histology is required to ensure that cases of malignancy are detected. However, penile SCC is an uncommon malignancy, accounting for <1% of male cancers [5,6]. Routine histology in circumcision should not be regarded as a method of detecting cases of carcinoma in situ as this may occur on the shaft, glans or prepuce [7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of progression to SCC is between 10 and 33 % (Graham and Helwig 1973 ). Rarely, cases of metastatic disease to the lymph nodes in the absence of an invasive component have been reported (Kim et al 2007 ).…”
Section: Clinical Presentationmentioning
confidence: 99%